Patent Protection for The National Interest - Nanda Dwi Rizkia; Hardi Fardiansyah (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
This research will analyze Patent Protection for the Interest of Indonesia. The approach used is normative law, to find the rule of law, legal principles, and legal doctrines in answering the legal issues at hand. This research will analyze the development of Intellectual Property Rights in essence is the development of Human Resources (HR), because IPR related to products and processes related to the IPR system is expected to develop HR, especially the creation of innovative, inventive culture. The role of intellectual property protection systems in relation to the protection of traditional knowledge, regarding how to preserve, protect and be fair in its use. Patent Protection is a matter of shared ownership of traditional knowledge.